Encoder and decoder modules of OCDM system using fiber-bragg grating (FBG) for metro area network - Shariffah Zarihan, Syed Zaharim Helmi (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org